Flocking on the web a case study on the applications of Twitter in disaster risk education and management for Marikina City residents - Salazar, Marianne V.; Yambao, Cyrill Beatriz; Encanto, Georgina R. (2012)
"This study assesses how microblogging site Twitter is being utilized to raise awareness and provide precautionary measures during disasters. Interviews with several news and government agencies revealed that their Twitter accounts are primarily used for quick and inexpensive information dissemination, as well as to promote citizen journalism among their followers. A survey on the Twitter usage of Marikina City residents showed that despite the efficiency and reliability of the site, social media still haven't surpassed the reach of broadcasting, which may also be reflected in the marked difference in the number of followers between Twitter accounts of news programs and those of newspapers. The citizens acknowledge that Twitter is really a good platform for immediate updates, but believe its target audience - who are mostly from the younger generation - is not enough to represent the entire community. Nonetheless, the findings of this study may encourage the local government of Marikina to maximize the potential of Twitter in becoming a powerful tool for disaster risk reduction and management."
Vita.
Undergraduate thesis (A.B.Journalism)--University of the Philippines, Diliman.
Keywords: Twitter; Online social networks -- Philippines